Ownership Concentration, Corporate Control Activity, and Firm Value: Evidence from the Death of Inside Blockholders - SLOVIN, MYRON B.; SUSHKA, MARIE E. (Journal of Finance, 1993)
ABSTRACT We analyze how ownership concentration affects firm value and control of public companies by examining effects of deaths of inside blockholders. We find shareholder wealth increases, ownership concentration falls, and extensive corporate control activity ensues. Share price responses are related to the deceased's equity stake. Control group holdings fall for two‐thirds of the firms due to either the estate's dispersal or inheritors selling stock. A majority of firms become targets of control bids: three‐quarters of bids are successful; one‐third are hostile. Our evidence is broadly consistent with Stulz's (1988) model of the relationship between ownership concentration and firm value.